A Qualitative Study on The Process of Corporate CultureInternalization for New Employees at PT Gapura Angkasa - Sofa Labera; Vezsa Levant Carents (Institut Komunikasi dan Bisnis LSPR, 2026)
This study explores the process of cultural value internalization among new employees at PT Gapura Angkasa, a leading ground handling service provider in Indonesia. Organizational culture, particularly the core values of AKHLAK (Amanah, Kompeten, Harmonis, Loyal, Adaptif, Kolaboratif), plays a vital role in shaping employee identity and work behavior. However, previous studies have mostly emphasized socialization mechanisms rather than employees’ subjective experience of internalization. Using a qualitative case study approach, data were collected through semi-structured interviews, limited observations, and document analysis involving new employees with less than one year of tenure. The findings reveal that onboarding provides effective initial exposure to corporate values, training translates these values into practical competencies, and mentoring strengthens relational support, enabling employees to embody the values personally. Respondents consistently reported that the AKHLAK values align with their personal identity and are reflected in their daily work behavior, fostering stronger engagement and collaboration. The study concludes that the integrating onboarding, training, and mentoring is essential for comprehensive cultural internalization. This synergy not only accelerates adaptation but also ensures that values are internalized beyond procedural compliance, supporting long-term organizational performance.